2020
DOI: 10.1016/j.vpoa.2020.100027
|View full text |Cite|
|
Sign up to set email alerts
|

Heartworm prevalence in dogs versus cats: Multiple diagnostic modalities provide new insights

Abstract: Highlights Prevalence of adult heartworm (HW) infection was 4 % in cats and 28 % in dogs. Combining antigen and antibody testing led to an overall 19 % positive cats. Prevalence did not differ between dogs and cats with added feline antibody testing. Dirofilaria repens microfilariae were identified in one dog and one cat. Acanthocheilonema reconditum microfilariae were identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Surveys of the number of dogs treated for heartworm are useful but cannot be directly compared to infection prevalence trends, and artificial increases in percent positive results can be seen when testing is used primarily for diagnostic verification of a suspected infection rather than for routine screening [ 28 , 29 ]. For example, the similar percent positive test results in dogs in Alaska (1.4%) and Florida (1.4%) in the present study likely reflect targeted testing by Alaska veterinarians based on a travel history compared to routine screening of dogs protected from infection by preventives despite intense transmission pressure in Florida [ 30 ]. Nonetheless, heartworm is a preventable infection, and the finding that 1.4% of pet dogs receiving veterinary care in the USA, or approximately 840,000 pet dogs overall, are identified as infected with this potentially fatal parasite each year, is dispiriting.…”
Section: Discussionmentioning
confidence: 64%
“…Surveys of the number of dogs treated for heartworm are useful but cannot be directly compared to infection prevalence trends, and artificial increases in percent positive results can be seen when testing is used primarily for diagnostic verification of a suspected infection rather than for routine screening [ 28 , 29 ]. For example, the similar percent positive test results in dogs in Alaska (1.4%) and Florida (1.4%) in the present study likely reflect targeted testing by Alaska veterinarians based on a travel history compared to routine screening of dogs protected from infection by preventives despite intense transmission pressure in Florida [ 30 ]. Nonetheless, heartworm is a preventable infection, and the finding that 1.4% of pet dogs receiving veterinary care in the USA, or approximately 840,000 pet dogs overall, are identified as infected with this potentially fatal parasite each year, is dispiriting.…”
Section: Discussionmentioning
confidence: 64%
“…The findings of this study, no observed cross-reactivity by A. reconditum post heat-ICD, agree with previous observations of previous studies using heat ICD in dogs where the heartworm status was unknown, only A. reconditum microfilariae were detected, and no antigen detected following post-heat ICD [ 3 , 35 ]. Recently in a study involving shelter animals from Florida, USA, 2 dogs with only A. reconditum microfilariae, initially tested “no antigen detected” but converted to post-heat ICD antigen positive [ 36 ]. Though the true heartworm status was unknown, those 2 dogs likely had occult heartworm infections resulting in the post-heat ICD positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Given the recent reports of D. repens in a shelter dog and cat from a Florida, USA shelter and unknown whether those cases were imported or were acquired locally, there is a need for a multiple diagnostic approach and increased awareness and surveillance particularly among sheltered animals [36]. It has been recognized that imported or travel related introduction of parasites to non-endemic areas are not uncommon and suggested that veterinarians should consider non-endemic parasites as differential diagnoses [21].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in St Kitts showed higher prevalence, 26% for T. felis and 22% for P. fastosum [ 8 ]. Regarding D. immitis , given that adult infections are rare in cats compared to dogs, the negative antigen tests were not unexpected [ 20 ]. The negative antibody tests might also be due to the spatial heterogeneous distribution of D. immitis on St Kitts [ 21 ] or the small sample size, especially since over half of the cats were on a heartworm preventative.…”
Section: Discussionmentioning
confidence: 99%